Bargaining with the CEO: The Case for "Negotiate First, Choose Second". Issue 4 (16th October 2018) - Korobkin, Russell; Dorff, Michael
Abstract : Whether chief executive officers (CEOs) and other senior executives are too highly compensated is one of the most publicized and divisive issues in corporate governance. In this article, we address this question not by asking whether executives are paid more than the value they create, but by asking whether firms could pay executives less money without reducing quality – thus retaining more money for shareholders–by using a better negotiation strategy. The focus of our attention is a particular feature of the way in which the compensation of CEOs and other high‐level employees is often determined, although rarely discussed: the firm first decides which candidate it prefers and only then negotiates the amount of compensation with the desired candidate. We hypothesize that this approach to negotiation, which we call "choose first, negotiate second, " is inferior to its alternative, which we call "negotiate first, choose second." We explain the theoretical basis for this hypothesis and then present the results of an experiment designed to test it. We conclude by suggesting a number of possible explanations for firms' failure to take advantage of what we consider to be a superior negotiating strategy.